Topics in Hydrometerology - V Hromadka II, Theodore; Rao, Prasada (IntechOpen, 2019)
The field of hydrometeorology bridges across both meteorology and hydrology. In this book, multiple experts present their work on various topics that fall under the purview of hydrometeorology. The chapters will provide readers with some of the latest developments and applications across different regions of the world and will motivate the audience to investigate other areas in hydrometeorology.